Design And Fabrication of Temperature and Humidity Stabilizer on Low Voltage Distribution Panel with PLC-Based Fuzzy Method to Prevent Excessive Temperature and Humidity on The Panel - Anggara Trisna Nugraha; Reza Fardiyan As'ad; Adianto; Vugar Hacimahmud Abdullayev (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Distribution panel is equipment that functions to receive electrical energy from PLN and subsequently distributes, as well as controls the distribution of electrical energy through the main and branch panel circuits to branch Distribution Panel or directly through the final load circuit. One of the problems with the Distribution Panel is the occurrence of fluctuating voltage changes and disturbances caused by condensation due to high humidity values. Based on previous research, the solution to minimize this problem is by optimizing the temperature and humidity on the Distribution Panel. So, in this research, we examine the effect of fan and heater control on the temperature and humidity of the Distribution Panel. The aim of this research is to fabrication the prototype that can be prevent the presence of excess temperature and humidity that does not meet applicable standards. So that it is expected to minimize the occurrence of hazards due to excessive temperature and humidity. In this research, it was found that the fan control using the fuzzy method can change the temperature of the panel room from 42.06oC to 32.82oC in a period of 440 seconds. However, the fan control with simple logic can only change the temperature of the panel room which is all 42.22oC to 35.05oC in 440 seconds. So it can be concluded that the fan control with the fuzzy method can reduce the temperature faster than the fan control with simple logic. Based on the graph on the panel room temperature stability test, it was found that the level of temperature stability in the room could be better controlled with fan control with the fuzzy method than using fan control with simple logic. Heater control system can reduce humidity levels from 95.14%RH to 55.25%RH within 160 seconds.